A comparative study of the pressureless sinterability of 3 mol% Y2O3-stabilized ZrO2 powders prepared by the sol–gel method under different synthesis conditions without modifiers - Mamana, Nadia (2014)
A wide set of 3 mol% Y2O3-stabilized ZrO2 (3YSZ) powders have been synthesized by the sol–gel method without modifiers from solutions of zirconium n-propoxide and yttrium acetate prepared with different water/Zr molar ratio and zirconium concentration, and the effect of these two synthesis variables on the pressureless sinterability of the 3YSZ powders has been investigated. It was found that the sinterability increases with increasing zirconium concentration and water/Zr molar ratio, which is attributed to the smaller cluster size developed during the sol–gel synthesis. Implications for the preparation of more sinterable 3YSZ powders are discussed